A padding method to reduce edge effects for enhanced damage identification using wavelet analysis. (February 2015) - Montanari, Lorenzo; Basu, Biswajit; Spagnoli, Andrea; Broderick, Brian M.
Abstract: Vibration response based structural damage identification by spatial wavelet analysis is widely considered a powerful tool in Structural Health Monitoring (SHM). This work deals with the issue of border distortions in wavelet transform that can mask tiny damages close to the boundary of a structure. Since traditional padding methods (e.g., zero-padding, symmetric padding, linear padding) are often not satisfactory, a simple and computationally inexpensive signal extension method, based on fitting polynomial functions and continuity conditions at the extrema, is proposed. The method is applied to analyze noisy mode shapes and static deflection of cracked cantilever and simply supported beams. The effectiveness and the versatility of the method in localizing tiny damages close to clamped, free or hinged beam boundaries is demonstrated. Furthermore, an extensive comparison with the linear padding method and Messina׳s isomorphism methods is carried out. Highlights: CWT edge effects in identifying damage close to beam ends are analyzed. New polynomial padding method, based on polynomial fitting functions, is proposed. Noisy mode shapes and static deflections of cracked beams are simulated. Proposed method is compared with literature padding methods.